2017
DOI: 10.2196/mhealth.7168
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Technology Interventions for Asthma Self-Management: Systematic Review and Meta-Analysis

Abstract: BackgroundMobile technology interventions (MTI) are becoming increasingly popular in the management of chronic health behaviors. Most MTI allow individuals to monitor medication use, record symptoms, or store and activate disease-management action plans. Therefore, MTI may have the potential to improve low adherence to medication and action plans for individuals with asthma, which is associated with poor clinical outcomes.ObjectiveA systematic review and meta-analysis were conducted to evaluate the efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 46 publications
3
51
1
2
Order By: Relevance
“…This review identified 16 studies that evaluated 15 theory-based digital interventions in Previous systematic reviews have shown that digital self-management interventions can be effective at improving clinical outcomes in asthma [12,30,31], and suggest that theorybased interventions may be more effective than interventions that have not used theory in their development [44]. To our knowledge, this is the first systematic review to examine the extent to which theory has been applied to the development of digital self-management interventions for asthma.…”
Section: Summary Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…This review identified 16 studies that evaluated 15 theory-based digital interventions in Previous systematic reviews have shown that digital self-management interventions can be effective at improving clinical outcomes in asthma [12,30,31], and suggest that theorybased interventions may be more effective than interventions that have not used theory in their development [44]. To our knowledge, this is the first systematic review to examine the extent to which theory has been applied to the development of digital self-management interventions for asthma.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Despite these benefits, adherence rates to asthma treatment remain low [12] and variable [13]. In general, 30-70% of people on long-term preventer therapy do not maintain the high levels of adherence necessary for good asthma control.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, some researchers have suggested that technology could help improve and support medication adherence among kidney transplant recipients [4,7]. The use and added benefits of information and communication technologies (ICT) to support daily adherence in other patient suffering from chronic conditions, such as cardiovascular diseases, asthma or HIV, are well documented [8][9][10].…”
Section: Introduction Backgroundmentioning
confidence: 99%